2020
DOI: 10.1177/1178223420962488
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic, Clinical, and Pathological Factors Influencing Outcomes in Locally Advanced Triple Negative Breast Cancer: A Brazilian Cohort

Abstract: Objective: To evaluate the association of sociodemographic, clinical, and pathological factors with response and survival in triple negative breast cancer (TNBC) undergoing neoadjuvant chemotherapy (NACT). Methods: Clinical-pathological and sociodemographic data were obtained from medical records of 235 eligible women with TNBC diagnosed between 2010 and 2014 undergoing NACT and surgery at the Brazilian National Cancer Institute. They have been assessed for pathological complete response (pCR), event-free surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…However, the literature indicates that there is no relationship between alcohol dependence and increased risk of TNBC 14 . Alcohol dependence is also associated with a worse chemotherapy response (first-line treatment for TNBC), worsening survival in these cases 15 . Alcohol-dependent patients in this study did not show a worse OS and/or DFS and an increased risk of mortality and/or recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…However, the literature indicates that there is no relationship between alcohol dependence and increased risk of TNBC 14 . Alcohol dependence is also associated with a worse chemotherapy response (first-line treatment for TNBC), worsening survival in these cases 15 . Alcohol-dependent patients in this study did not show a worse OS and/or DFS and an increased risk of mortality and/or recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…These patients also exhibited a high prevalence rate of obesity, higher Ki67 score, as well as LVI and PNI, all of which are traditional prognostic factors for poorer outcomes in breast cancer patients. 23,24 Additionally, RCB, an outcome used to determine the volume of residual disease after NACT with well-known strong impact on patient survival, displayed similar proportions among HER2 subgroups. 25 That said, the pattern of response to NACT in patients with TNBC might be independent of HER2 expression status by IHC.…”
Section: Discussionmentioning
confidence: 89%
“…Although several studies indicate that the addition of platinum drugs to the neoadjuvant regimens could increase pathological complete response 35 , 36 , few patients were treated with such drugs during the time range evaluated in this study period (2014–2017). For patients receiving NAT, Silva et al reported that the most common regimens used are AC-T and FAC-T (fluorouracil plus doxorubicin plus cyclophosphamide followed by docetaxel) 13 . Herein, we also observed AC-T as the main combination regimen in the neoadjuvant setting.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, TNBC is most detected in stage III, with lymphocytic infiltration, multifocality, and tumor size > 2 cm at diagnosis 12 , 13 . Compared to other BC subtypes, a higher proportion of patients with TNBC undergo radical surgery and chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation